NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Common genetic variants associate with serum phosphorus concentration. - Kestenbaum, Bryan; Glazer, Nicole L; Köttgen, Anna; Felix, Janine F; Hwang, Shih-Jen; Liu, Yongmei; Lohman, Kurt; Kritchevsky, Stephen B; Hausman, Dorothy B; Petersen, Ann-Kristin; Gieger, Christian; Ried, Janina S; et al. (J Am Soc Nephrol, 2010)
Phosphorus is an essential mineral that maintains cellular energy and mineralizes the skeleton. Because complex actions of ion transporters and regulatory hormones regulate serum phosphorus concentrations, genetic variation may determine interindividual variation in phosphorus metabolism. Here, we report a comprehensive genome-wide association study of serum phosphorus concentration. We evaluated 16,264 participants of European ancestry from the Cardiovascular Heath Study, Atherosclerosis Risk in Communities Study, Framingham Offspring Study, and the Rotterdam Study. We excluded participants with an estimated GFR <45 ml/min per 1.73 m(2) to focus on phosphorus metabolism under normal conditions. We imputed genotypes to approximately 2.5 million single-nucleotide polymorphisms in the HapMap and combined study-specific findings using meta-analysis. We tested top polymorphisms from discovery cohorts in a 5444-person replication sample. Polymorphisms in seven loci with minor allele frequencies 0.08 to 0.49 associate with serum phosphorus concentration (P = 3.5 x 10(-16) to 3.6 x 10(-7)). Three loci were near genes encoding the kidney-specific type IIa sodium phosphate co-transporter (SLC34A1), the calcium-sensing receptor (CASR), and fibroblast growth factor 23 (FGF23), proteins that contribute to phosphorus metabolism. We also identified genes encoding phosphatases, kinases, and phosphodiesterases that have yet-undetermined roles in phosphorus homeostasis. In the replication sample, five of seven top polymorphisms associate with serum phosphorous concentrations (P < 0.05 for each). In conclusion, common genetic variants associate with serum phosphorus in the general population. Further study of the loci identified in this study may help elucidate mechanisms of phosphorus regulation.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Fibroblast Growth Factors; Gene Frequency; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Male; Middle Aged; Phosphorus; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing; Sex Factors; Sodium-Phosphate Cotransporter Proteins, Type IIa

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

An Empirical Comparison of Joint and Stratified Frameworks for Studying G × E Interactions: Systolic Blood Pressure and Smoking in the CHARGE Gene-Lifestyle Interactions Working Group. - Sung, Yun Ju; Winkler, Thomas W; Manning, Alisa K; Aschard, Hugues; Gudnason, Vilmundur; Harris, Tamara B; Smith, Albert V; Boerwinkle, Eric; Brown, Michael R; Morrison, Alanna C; Fornage, Myriam; Lin, Li-An; et al. (Genet Epidemiol, 2016)
Studying gene-environment (G × E) interactions is important, as they extend our knowledge of the genetic architecture of complex traits and may help to identify novel variants not detected via analysis of main effects alone. The main statistical framework for studying G × E interactions uses a single regression model that includes both the genetic main and G × E interaction effects (the "joint" framework). The alternative "stratified" framework combines results from genetic main-effect analyses carried out separately within the exposed and unexposed groups. Although there have been several investigations using theory and simulation, an empirical comparison of the two frameworks is lacking. Here, we compare the two frameworks using results from genome-wide association studies of systolic blood pressure for 3.2 million low frequency and 6.5 million common variants across 20 cohorts of European ancestry, comprising 79,731 individuals. Our cohorts have sample sizes ranging from 456 to 22,983 and include both family-based and population-based samples. In cohort-specific analyses, the two frameworks provided similar inference for population-based cohorts. The agreement was reduced for family-based cohorts. In meta-analyses, agreement between the two frameworks was less than that observed in cohort-specific analyses, despite the increased sample size. In meta-analyses, agreement depended on (1) the minor allele frequency, (2) inclusion of family-based cohorts in meta-analysis, and (3) filtering scheme. The stratified framework appears to approximate the joint framework well only for common variants in population-based cohorts. We conclude that the joint framework is the preferred approach and should be used to control false positives when dealing with low-frequency variants and/or family-based cohorts.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Large-scale exome array summary statistics resources for glycemic traits to aid effector gene prioritization. - Willems, Sara M; Ng, Natasha H J; Fernandez, Juan; Fine, Rebecca S; Wheeler, Eleanor; Wessel, Jennifer; Kitajima, Hidetoshi; Marenne, Gaelle; Sim, Xueling; Yaghootkar, Hanieh; Wang, Shuai; Chen, Sai; et al. (Wellcome Open Res, 2023)
BACKGROUND: Genome-wide association studies for glycemic traits have identified hundreds of loci associated with these biomarkers of glucose homeostasis. Despite this success, the challenge remains to link variant associations to genes, and underlying biological pathways. METHODS: To identify coding variant associations which may pinpoint effector genes at both novel and previously established genome-wide association loci, we performed meta-analyses of exome-array studies for four glycemic traits: glycated hemoglobin (HbA1c, up to 144,060 participants), fasting glucose (FG, up to 129,665 participants), fasting insulin (FI, up to 104,140) and 2hr glucose post-oral glucose challenge (2hGlu, up to 57,878). In addition, we performed network and pathway analyses. RESULTS: Single-variant and gene-based association analyses identified coding variant associations at more than 60 genes, which when combined with other datasets may be useful to nominate effector genes. Network and pathway analyses identified pathways related to insulin secretion, zinc transport and fatty acid metabolism. HbA1c associations were strongly enriched in pathways related to blood cell biology. CONCLUSIONS: Our results provided novel glycemic trait associations and highlighted pathways implicated in glycemic regulation. Exome-array summary statistic results are being made available to the scientific community to enable further discoveries.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins